Os desafios na difusão de inovações tecnológicas: o caso dos bioplásticos - Barbato, Andrey Gustavo (2021)
The objective of this work is to understand, based on the presented theory, what are the intervening factors (with emphasis on the challenges) in the diffusion of bioplastics as raw material of the Brazilian plastics industry. Thus, it is intended to contribute to a better understanding of the barriers imposed in the diffusion process, in favor of alternative propositions. To this end, the literature review on the diffusion of technological innovations and how to divide themselves as main schools of thought that study the theme - the conventional neoclassical and the evolutionary neoschumpeterian - is presented. Based on the instruments obtained in the theory and state of the art of the object of study, we seek to understand the perceptions of business agents inserted in the production chain of plastic and bioplastic, from the producer of the basic input to the consumer company of plastic packaging, so that we could confront the different points of view present in the market. We identified that the supply factor has a relevant role and proves to be a barrier due to the monopoly in the supply of raw materials. The use of biopolymers in applications with low added value also generate disputes in the sector for their appropriation and compromise an interaction between companies, in addition to the issue of recycling and biodegradability, which are fundamental points to move forward and thus contribute to the solution of problems related to the use of plastics